The Relationship between Socio-Economic Factors, Mother's Knowledge of Healthy Environment and Diarrhea with the Incidence of Diarrhea in Toddlers Aged 1-5 Years at Puskesmas Pembina Palembang - Arly Febrianti (Institute of Computer Science (IOCS), 2018)
Diarrhea is the main cause of pain and death in, children in the developing world with an estimated billion episodes of 1.3 3.2 and million deaths every year in toddlers. Drurhea is the increasing volume of, and a greater frequency than dilution 3. times a day The purpose of this research is to find the factors of knowledge about the environment and healthy, and diarrhea as the socio-economic diarrhea in children under five years of age 1-5 centers. palembangThe population of the research is all mothers have toddlers 1-5 age years going to the health center trustees 59. toddlers in palembangTechnical the sample in research is the, sampling so samples were obtained 59. oneThe results of research on economic factors respondents found that of respondents 59 obtained p value = 0, 033 while this knowledge about the environmental health was found that out of respondents 59 obtained p value = 0.045 and knowledge factor. Poverty, of environmental health and knowledge of a person greatly affects the status of health in children under five years old .Is statistically there was a correlation between factors of economy with an instance of diarrhea in children under five years old, there was a correlation between other factors than a fuel mommy about the level of knowledge of healthful environment with an instance of diarrhea in toddler and he was there was a correlation between the level of knowledge of mommy about frequent bouts of diarrhea with the incident when the town diarrhea in children under five years old.